Prasugrel vs clopidogrel in cardiogenic shock patients undergoing primary PCI for acute myocardial infarction - Orban, Martin; Mayer, Katharina; Morath, Tanja; Bernlochner, Isabell; Hadamitzky, Martin; Braun, Siegmund; Schulz, Stefanie; Hoppmann, Petra; Hausleiter, Jörg; Tiroch, Klaus; Mehilli, Julinda; Schunkert, Heribert; Massberg, Steffen; Laugwitz, Karl-Ludwig; Sibbing, Dirk; Kastrati, Adnan (Thrombosis and Haemostasis, 2014)
There is limited clinical data comparing different P2Y12-receptor inhibitors in patients with acute myocardial infarction (AMI) complicated by cardiogenic shock. The aim of the ISAR-SHOCK registry was to compare the clinical outcome of patients treated with clopidogrel vs prasugrel in this setting. Patients (n=145) with AMI complicated by cardiogenic shock and undergoing primary PCI in two centres (Deutsches Herzzentrum München and Klinikum rechts der Isar, Technical University Munich) between January 2009 and May 2012 were included in this registry. The use of prasugrel for patients within this registry reflected co-morbidities and platelet function testing results during the acute AMI phase. Early outcome at 30-days was reported with regard to all-cause mortality, myocardial infarction (MI), stent thrombosis (ST) and bleeding events. With regard to antiplatelet treatment in the 145 cardiogenic shock patients, 50 patients were initially treated or immediately switched to prasugrel while 95 patients were treated with clopidogrel. All-cause mortality was lower in prasugrelvs clopidogrel-treated patients (30 % vs 50.5%, HR: 0.51, 95% CI [0.29–0.92], p=0.025). No significant differences in prasugrel- vs clopidogrel-treated patients were observed for the occurrence of MI (p=0.233), ST (p=0.306) or TIMI major bleedings (p=0.571). Results of the ISAR-SHOCK registry suggest that the use of prasugrel in AMI patients complicated by cardiogenic shock might be associated with a lower mortality risk as compared to clopidogrel therapy without increasing the risk of bleeding. These findings, however, need confirmation from specifically designed randomised studies in this high-risk cohort of patients.
Keywords: Clopidogrel; prasugrel; cardiogenic shock; bleeding; mortality